APOCALYPTIC NARRATIVE SCHEMAS IN DYSTOPIAN FILMS - Muwaffaq, Thafhan; Komar, Nurul; Armandaru, Rio (International Journal of Humanity Studies (IJHS), 2020)
This research investigates the way dystopia as film genre is attributed with catastrophe or, what will be regarded here as apocalyptic events. We question the way in which the genre represents state of affairs of humanity in the face of catastrophe, in catastrophe, and after catastrophe. We conducted a narrative analysis under the account of semiotic cognitive approach, by identifying narrated events, and actions of the protagonist as constituting parts of event. We argue that narrative in dystopian films represent three types of apocalyptic schema (i.e. pre-apocalyptic, apocalyptic, and post-apocalyptic). Each schema seems to have distinct model of storyline, regardless of the predefined genre of the film (e.g. adventure, sci-fi, fantasy, etc.). Despite the distinct schemas, the analyzed films illustrate typical tone of hopefulness wherein humanity prevails over catastrophe and dystopian state of affairs. Another typical representation in dystopian films analyzed here is portrayal of collective fear among the protagonist. Our study leads to a point that humanity is portrayed adaptive to catastrophic situations, therefore it is able somehow to survive. Here we offer narrative standard in dystopia genre with the light of cognitive semiotics perspective, which differs to a great degree with theories offered by classical literary studies.